Penerapan Metode Analytic Network Process (ANP) untuk Mengatasi Keterlambatan Pengadaan Barang pada Bagian Umum di PT Solo Grafika Utama - Aris Wahyu Nugroho; Rizqy Widhianggitasari; David Fu’ani Priadi; Pringgo Widyo Laksono (Performa: Media Ilmiah Teknik Industri, 2016)
Procurement  activities of raw materials is one of the vital activity for the company. PT Solo Grafika Utama is one of the companies that rely heavily on this procurement activity for a smooth production. Until now PT Solo Grafika Utama has been working with several suppliers in the procurement of raw materials production. However, in practice, these activities often experience problems such late delivery by suppliers for various things. As a result of delays in the procurement materials  makes the production process is hampered or delayed, so the time that required for production process exceeded the production schedule planning that has been set before. This resulted in the delivery of products to consumers experienced delays and it makes them are not satisfied with the performance of the company. Therefore we need an analysis to determine the factors that cause  the delay. Once the cause is known, we need a follow-up analysis in order for the supplier selection decision making process of  PT Solo Grafika Utama using ANP method. Supplier selection decision-making process of the raw materials in PT. Solo Grafika Utama involves many criteria and sub-criteria assessment which is then compared and processed to obtain the supplier with the highest value and become preferred suppliers for the company.